The choroid and lamina cribrosa is affected in patients with Parkinson's disease: enhanced depth imaging optical coherence tomography study - ÇERMAN, EREN; ÇELİKER ATABERK, HANDE; ERASLAN, MUHSİN; ŞAHİN, ÖZLEM (WILEY, 2016)
Purpose: To compare lamina cribrosa (LC) and choroidal thicknesses using enhanced depth imaging optical coherence tomography (EDI-OCT) in patients with Parkinson's disease (PD) and healthy controls. Methods: A total number of 44 eyes of 22 patients with PD and 50 eyes of 25 healthy subjects were utilized in this institutional cross-sectional study. After a complete ophthalmic examination, all eyes were imaged with OCT (RTVue-100 version 5.1 Fourier-domain optical coherence tomography; Optovue Inc., Fremont, CA, USA); LC and choroidal thickness were assessed. Results: The mean LC thicknesses were 209.4 +/- 40.2 mu m in patients with PD and 292.5 +/- 33.7 mu m in control subjects. There was a significant difference in the mean LC thickness between the groups (p < 0.0001). The choroidal thickness measurements of the PD group at the subfoveal region and 1.5 mm temporal and 1.5 mm nasal to the fovea were 228.1 +/- 44.3, 193.2 +/- 41.4 and 188.4 +/- 49.0 lm, respectively, whereas measurements for the controls were, respectively, 246.5 +/- 38.2, 227.3 +/- 34.7 and 216.7 +/- 51.4 lm. The choroid was significantly thinner in eyes of the PD group compared to that of the controls (p = 0.001, p < 0.001, and p = 0.006). There was no significant correlation between the disease severity and OCT parameters. The duration of the disease showed a statistically significant negative correlation with LC (rs[94] = -0.700, p < 0.001), and average subfoveal and temporal and nasal choroid thicknesses (rs[94] = -0.282, p = 0.006; rs[94] = -0.324, p = 0.001, rs[94] = -0.240, and p = 0.020, respectively). Conclusions: Regardless of the disease severity, PD may cause atrophy and volume loss in the lamina cribrosa, and choroid. An enhanced depth imaging technique may be used as an additional modality in the diagnosis and follow-up of patients with PD.
Keywords: choroidal thickness; enhanced depth imaging; enhanced depth imaging; lamina cribrosa; optical coherence tomography; Parkinson's disease; retinal nerve fibre layer; RNFL; CENTRAL SEROUS CHORIORETINOPATHY; MILD COGNITIVE IMPAIRMENT; OCULAR PERFUSION-PRESSURE; ALZHEIMERS-DISEASE; MACULAR DEGENERATION; NERVE HEAD; ORTHOSTATIC HYPOTENSION; MULTIPLE-SCLEROSIS; RETINAL PATHOLOGY; DIURNAL-VARIATION